Nature and performance of Portuguese Real Estate Investment Funds - Vasques, F. (2007)
Portuguese Real Estate Investment Funds are twenty years old and currently growing at unprecedented pace. Tax benefits and current market circumstances are the main drivers of interest on this type of institutional investment. In this paper a characterization and analysis of their nature, and a comparison against other indirect property investment vehicles is presented. Issues Iike structure, valuation, management, regulations and economical importance are addressed. A study of total return time series, covering trend analysis, descriptive statistics and return distributions, is developed. Evidence of the importance of endogenous factors in performance explanation and conclusiveverification of non-normality in return distributions are presented, pointing towards the need of further research on predictability issues.